Considerations for Integrating Women into Closed Occupations in the U.S. Special Operations Forces - Szayna, Thomas S. (RAND Corporation, 2015)
Integrating women into special operations forces poses potential challenges for unit cohesion. The potential integration of women raises issues of effectiveness, in terms of physical standards and ensuring the readiness, cohesion, and morale essential to high-performing teams. This report assesses those challenges and provides analytical support for validating occupational standards for positions controlled by U.S. Special Operations Command.